Synthetic Mimics of Antimicrobial Peptides for the Targeted Therapy of Multidrug‐Resistant Bacterial Infection. Issue 22 (19th August 2021) - Gong, Chenyu; Sun, Junjie; Xiao, Yan; Qu, Xue; Lang, Meidong
Abstract: Antibacterial materials are highly demanded in treatment of bacterial infection, especially severe ones with multidrug‐resistance. Herein, pH‐responsive polypeptide, i.e., poly‐L‐lysine modified by 1‐(propylthio)acetic acid‐3‐octylimidazolium and citraconic anhydride (PLL‐POIM‐CA), is synthesized by post‐polymerization modification of poly‐L‐lysine (PLL) with 1‐(propylthio)acetic acid‐3‐octylimidazolium (POIM) and citraconic anhydride (CA). It is observed that PLL‐POIM‐CA is stable under normal physiological condition, while CA cleaves rapidly at weakly acidic environment like bacterial infectious sites. The hydrolyzed PLL‐POIM‐CA exhibits excellent broad‐spectrum antibacterial activities against Gram‐negative bacteria of Escherichia coli and Gram‐positive bacteria of Staphylococcus aureus and methicillin‐resistant Staphylococcus aureus (MRSA). In particular, the minimum inhibitory concentration (MIC) against multidrug‐resistant bacteria like MRSA is as low as 7.8 µg mL −1 . Moreover, PLL‐POIM‐CA exhibits good biocompatibility with mouse fibroblast cells (L929) in vitro and improved hemocompatibility with an HC50 exceeding 5000 µg mL −1 . Therefore, PLL‐POIM‐CA displays an excellent bacteria versus cells selectivity (HC50 /MIC) over 534, which is 53 times higher than natural antimicrobial peptide of indolicidin. It is further demonstrated in vivo that the antimicrobial polypeptide effectively accelerates MRSA‐infected wound healing by relieving local inflammatory response. Therefore, this targeted antimicrobial polypeptide has broad application prospects for the treatment of multidrug‐resistant bacterial infection. Abstract : Inspired by natural antimicrobial peptides, a novel pH‐responsive antibacterial polypeptide (PLL‐POIM‐CA) is synthesized with high activities in vitro and in vivo against multidrug‐resistant bacteria. More importantly, this biodegradable antibacterial polypeptide targets infected wounds and accelerates wound healing, which provides a new strategy for the development of targeted antibacterial materials.